Sensitive Logic in Campo Minado y Teatro de Guerra de Lola Aria [Lógicas Sensibles en Campo Minado y Teatro de Guerra de Lola Arias] - Hernández-Parraguez, C (Universidad de los Lagos, 2020)
Into the postdramatic theater the mimetic funtion of the body tends to be displaced towards transmedial resources thus favoring the producction of a metatheatre. The Lola Arias’s work stands out precisely because of putting in tension the role of the acting body on stage producing, through transmedial resources, a representational crisis that questions traditional forms of drama. The present article aims to establish the aesthetic strategies used by this playwright and director to problematize the place of the body in her theatral work Campo Minado (2016) and her documentary Teatro de Guerra (2018). © 2020, Universidad de los Lagos. All rights reserved.